2017
DOI: 10.1103/physreve.95.062133
|View full text |Cite
|
Sign up to set email alerts
|

Log-log growth of channel capacity for nondispersive nonlinear optical fiber channel in intermediate power range

Abstract: We consider a model nondispersive nonlinear optical fiber channel with an additive Gaussian noise. Using Feynman path-integral technique, we find the optimal input signal distribution maximizing the channel's per-sample mutual information at large signal-to-noise ratio in the intermediate power range. The optimal input signal distribution allows us to improve previously known estimates for the channel capacity. We calculate the output signal entropy, conditional entropy, and per-sample mutual information for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(63 citation statements)
references
References 20 publications
4
59
0
Order By: Relevance
“…We have also shown that our result for the spectral efficiency (50) for nonzero dispersion approaches the expression (52) derived in Ref. [12] in the case when β tends to zero.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We have also shown that our result for the spectral efficiency (50) for nonzero dispersion approaches the expression (52) derived in Ref. [12] in the case when β tends to zero.…”
Section: Discussionsupporting
confidence: 87%
“…It has been observed that the spectral efficiency of the nonlinear channel decreases with increasing SNR at high enough values of SNR [3][4][5]7]. This analysis certainly provides only a lower bound on channel capacity and does not prove that the Shannon nonlinear fiber channel capacity is decreasing with power; see, for example, discussions in [8][9][10][11][12]. As a matter of fact, the decrease of the spectral efficiency can be linked to different effects.…”
Section: H[y |X] = − Dxdy P [X]p [Y |X] Log P [Y |X] (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore as the first step in understanding of the effects of nonlinearity impact in the channel one can consider the nonlinear channel with zero average dispersion. The nonlinear nondispersive optical fiber channels are also considered in numerous papers, see, e.g., * Electronic address: panarin.a.a@mail.ru † Electronic address: a.v.reznichenko@inp.nsk.su ‡ Electronic address:i.s.terekhov@gmail.com [13][14][15][16][17][18]. Of course, the problem of capacity calculation for these channels is simpler than the problem with dispersion.…”
mentioning
confidence: 99%